Cell-Line–Specific Cytotoxic and Antiproliferative Effects of Citrinin in A549 and HCT-116 Cells - Aygördü, Arda Oğuz; Bükrek, Arda; Salci, Seher; Kürçe, Buse Elif; Yüce, Hande; Özek, Dilan Aşkın; Ünüvar, Songül (İnönü Üniversitesi, 2026)
Citrinin (CIT) is a mycotoxin commonly found in foods and has been linked to toxicity in various cell types. In our study, we examined how CIT affects human lung adenocarcinoma (A549), colorectal cancer (HCT116), and healthy fibroblast (L929, used as a control) cells. Our MTS assays revealed that CIT reduced cell viability in a manner dependent on both dose and exposure time. Interestingly, HCT116 cells were more sensitive to CIT than A549 cells, suggesting that its effects can vary between cancer types. We also performed wound healing experiments to assess cell migration and proliferation. CIT significantly slowed these processes in cancer cells, while fibroblasts were less affected. These results indicate that CIT can hinder cancer cell spread, though not without affecting normal cells. Previous studies have proposed several mechanisms for CIT’s toxicity. It appears to promote apoptosis by generating reactive oxygen species, disrupting mitochondrial membrane potential, activating caspases, and inducing endoplasmic reticulum stress. While these anticancer effects are promising, CIT’s high toxicity to normal cells and limited selectivity remain major hurdles for therapeutic use. Overall, our findings shed light on CIT’s cytotoxic and antimigratory actions, emphasizing the need for further research to identify doses that maximize its anticancer potential while minimizing harm to healthy cells.
Keywords: Genotoxicity and Cytotoxicity; Genotoksisite ve Sitotoksisite; Pharmaceutical Toxicology; Farmasotik Toksikoloji